Coagulation Factor 1, Oxidative Stress Marker And Antioxidant Level In Predicting The Outcome Of Diabetic Foot Ulcer (International Journal of Food and Nutritional Sciences, 2022)
INTRODUCTION:Diabetic Foot Ulcer is the complication of diabetes mellitus that impacts heavily on the quality of life. Diabetic foot ulcer is considered as the most important cause of lower extremity amputation.The pathogenesis of diabetic foot ulcer is multifactorial and complex.It is associated with microvascular and macrovascular complications. Oxidative stress marker plasma Malondialdehyde(MDA) plays an important role in the pathogenesis of diabetic foot ulcer. Coagulation factor 1 Fibrinogen plays an important role as the inflammatory marker of vascular changes and endothelial dysfunction.AIM & OBJECTIVE:The aim of the study is to assess and correlate the levels of vitamin C , Plasma Fibrinogen &Plasma MDA with prognosis in diabetic foot ulcer patients Grade 1&2 and along with healthy controls.MATERIALS &METHODS:This study includes 100 Diabetic patients (30 without complication, 35 diabetic foot ulcer Grade1&35 with grade 2) and 30 age matched healthy controls. After getting informed consent from the patient , 5ml of venous blood sample was collected in EDTA coated tube. Plasma MDA was assayed by Esterbauer and Steinberg method. Plasma Fibrinogen was measured in mispa coagulometer. Plasma Vitamin C was measured by Roe & Kuether method . HbA1C was calculated for all the subjects by Draca fully automated analyser. haemoglobin was measured in Sahli’s hemoglobinometerRESULTS:Oxidative stress marker and Plasma Fibrinogen levels were markedly increased in Grade 2 ulcer patients followed by Grade 1 patients and diabetes without complications. Plasma levels of vitamin C significantly reduced in grade 1 and 2 diabetic foot ulcer patients .CONCLUSION: Poor prognosis of diabetic foot ulcer can be explained by the increased levels of Oxidative stress and Coagulation Factor1 and decreased levels of vitamin C irrespective of Glycemic control.